Dysfunctional uterine bleeding in adolescent girls and evaluation of their response to treatment - Başaran, Halide Özge; Akgül, Sinem; Öksüz-Kanbur, Nuray; Gümrük, Fatma; Cetin, Mualla; Derman, Orhan (The Turkish Journal of Pediatrics, 2013)
Dysfunctional uterine bleeding (DUB) is a gynecologic problem that occurs often during adolescence and is the most frequent cause of urgent admission to the hospital. DUB occurs in the adolescent usually because of anovulation, a result of developmental immaturity of the hypothalamic-pituitary-ovarian (HPO) axis. Diagnosis can only be confirmed when there is no other pathology present, so it is important to exclude all the other possibilities. The aim of this study was to evaluate the frequency of coagulation disorders and other underlying situations as a cause of menorrhagia in adolescents with DUB and to assess the response to the treatment(s) given.